Interprofessional Collaborative Practice Improves Access to Care and Healthcare Quality to Advance Health Equity. Issue 5 (September 2022) - White-Williams, Connie; Bittner, Vera; Eagleson, Reid; Feltman, Morgan; Shirey, Maria
ABSTRACT: Healthcare disparites exist in cardiovascular care, including heart failure. Care that is not equitable can lead to higher incidence of heart failure, increased readmissions, and poorer outcomes. The Heart Failure Transitional Care Services for Adults Clinic is an interprofessional collaborative practice that provides guideline-directed medical therapy and education to underserved patients with heart failure. Little is known regarding healthcare equity and quality metrics in relation to interprofessional teams. Thus, the purpose of this study was to examine if an interprofessional collaborative practice care delivery model can affect access to care and healthcare quality outcomes in underserved patients with heart failure. As evidenced by control charts over a two and a half year period, the Heart Failure Transitional Care Services for Adults Clinic was able to show improvements in access to care and quality metrics results without variation. An interprofessional collaborative practice can be an effective delivery model to address health equity and quality of care outcomes.